Acceptability of Environmental Education Kit (EE KIT) among teachers at selected schools in Peninsular Malaysia - Sulaiman, Siti Hajar (2014)
This study includes both the qualitative and quantitative analyses. A qualitative study was conducted in an attempt to assess the use of the Environmental Education Kit (EE Kit) among teachers in Peninsular Malaysia. The study was conducted on teachers from four selected secondary schools, representing four school zones in Malaysia in April and May 2011. The study is carried out because of the lack of EE tools to help teachers to deliver EE at schools. Data was collected through face-to-face interviews. Responses from the in depth interview will used to construct the questions for the survey. Of the 85 teachers, fifteen of them volunteered to be interviewed. This study aimed to describe and analyze the experience of using the EE Kit for teaching environmental education in schools. The teacher’s acceptability of the EE Kit is described in terms of four themes: teachers' perception; teachers’ receptiveness; frequency of use; and factors influencing its use. This study revealed 73% (11/15) of the interviewee have a positive view towards using the EE kit. In the quantitative analysis, three indicators were developed to measure the teachers’ acceptability of the EE Kit: Perception, Attitude and Receptiveness. In this study, 81 teachers teaching Science, Geography, English and Malay Language from four public schools in Peninsular Malaysia who received the EE Kit participated. This study found that, 75/81 (92.59%) knew about the EE Kit, 64/81 (79.01%) used the EE Kit and 11 (13.58%) who knew about the kit but did not use it. This study revealed that teachers positive attitude and perception are positively related to their acceptance towards the EE Kit practice as well as inclination responsible towards environment. The exploratory analysis using the Principal Component Analysis (PCA) indicate the following: 1) The teachers welcome the idea of new methods of teaching which was described as ‘innovative’ and ‘new ideas’ and at the same time ‘imparting environmental values to students’; 2) The teachers are supportive of the EE Kit because they see it as valuable teaching tools in assisting their teaching EE component; and 3) The teachers are more receptive to using the EE Kit because they have strong beliefs on the importance of knowing the environment, the value of EE in influencing student behaviour, they have the strong sense of responsibility towards the environment and their interest in environmental issues. From this study, seven factors were identified as barriers to implementing EE Kit in the classroom: (1) technical difficulties (2) limited resources (3) Not enough time to do in class (4) Language barrier (5) Limited access to the EE Kit (6) Lack of training and (7) Other factors (Figure 4.4). Time constraint and lack of training seemed to be the top two highest complaints from the teachers. Similar results were obtained from the qualitative studies and this finding is affirmed in this study. Overall, 79% of the teachers are using the EE Kit in the classroom and recommend it to be used in all schools in Malaysia. Two important issues should be given great consideration before introducing the EE Kit nationwide: (1) the need for teacher training on the use of EE Kit, and (2) revising the EE Kit content making it easier for all students, especially for academically as well as linguistically challenged.